STRATEGI POLITIK NAHDLATUL ULAMA DI ERA ORDE BARU - Shobacha, Nurul (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
This article aims to elaborate the political’s strategy of Nahdlatul Ulama (NU) in the New Order. NU has a long history at political history in Indonesia. The findings showed that relation between NU and the state always up and downs. In the Old Order, NU became a large Islamic organization in Indonesia, in addition became a political party. In this era, because of simplification of political parties, NU joined to Partai Persatuan Pembangunan (PPP). Unfortunately, NU was being weak because PPP had been dominated with Islamic modern groups. NU back to Khittah 1926 and back to the beginning of agreement in the Old Order era. NU decided for focusing in education field.